Evaluation Model of Sports Culture Industry Competitiveness Based on Fuzzy Analysis Algorithm. (28th April 2022) - Sun, Guoqiang; Zhang, Xinxin; Lin, Yu
Abstract : Since reform and opening, our country's sports and cultural industries have grown from nothing. Due to the complexity of the evaluation factors and methods used to determine the competitiveness of the sports cultural industry, this paper establishes a seven-dimensional sports cultural industry competition based on the integration and development of the sports tourism industry and national culture, drawing on the theory and methods used to determine the tourism industry's competitiveness. Based on a fuzzy analysis algorithm, we developed a system for evaluating strength and a model for evaluating the competitiveness of the sports culture industry. According to the results of the evaluation of the competitiveness of the sports culture industry in numerous regions of China, the evaluation method proposed in this paper is superior to the traditional evaluation method and has contributed to the development of China's sports culture industry.